Bio-chemical recovery of valuable metals from Indian Ocean nodules in presence of pyrite and sulphur - Mehta K.D.; Pandey B.D.; Mankhand T.R. (My University, 2025)
The biodissolution of copper, nickel and cobalt from the Indian Ocean manganese nodules has been investigated in presence of pyrite and elemental sulphur using Thiobacillus ferrooxidans (Tf) and Thiobacillus thiooxidans (Tt) as the microorganisms. The leaching of manganese nodules proceeds with reduction of Mn4+ to Mn2+ by ferrous ions generated from pyrite and H2SO3 generated from that of sulphur by bacterial action. Breaking the lattice structure of manganese and iron based minerals like todorokite, birnessite, lithiophorite and goethite by chemico-bacterial action, releases the valuable metals such as copper, nickel and cobalt thereby dissolving them in the aqueous solution. Recovery of the metals was highest for finer size (-75 μm) fraction of the nodules. In presence of 10% pyrite at 5% pulp density, pH 2.0 and 303 K temperature, 97% Cu, 85% Ni, and 55% Co were leached in 50 days. However, with the coarser particle size of -300 + 200 μm, the metal recoveries at 303 K were 81% Cu, 67% Ni and 39% Co in 50 days time in presence of pyrite. Under these conditions 61% Cu, 58% Ni and 26% Co dissolution was observed in presence of sulphur. Raising the temperature from 293 to 308 K increased the metal recovery.